Understanding computers in a changing society - Morley, Deborah (Course Technology, Cengage Learning, 2013)
Understanding Computers in a Changing Society gives your students a classic introduction to computer concepts with a modern twist! Known for its emphasis on basic computer concepts and societal issues, this text makes concepts relevant to today's career-focused students and has increased emphasis on mobile computing and related issues such as mobile commerce and mobile security